The Effect of Ethanol Vapor and Chitosan Coating on Quality and Shelf Life of Mangosteen (Garcinia Mangostana L. - Pradika, Kadek Arista; Utama, I Made Supartha; Tika, I Wayan (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
Mangosteen is a tropical fruit with a high potential to be an export commodity, but the problem is that it quickly declines in quality due to its postharvest physiological process. The purpose of this study was to determine the effectiveness of ethanol vapor treatment and chitosan coating in slowing down quality deterioration and extending the shelf life of mangosteen fruit. Analysis used a factorial completely randomized design with two treatment factors. The first factor was giving ethanol vapor from the evaporation of ethanol solution with concentrations of 0%, 5%, and 10%; and the second factor was chitosan coating with concentrations of 0%, 1.25%, and 1.5%. The parameters were weight loss, the intensity of damage, color difference, fruit hardness, total acid value, total dissolved solids, and organoleptic tests on the color of the flesh, the flesh taste, and the flesh aroma. Observations were for 25 days of storage at room temperature (28- 31ºC). The results showed that the single application of ethanol vapor had a significant effect on weight loss, while the single chitosan coating had a significant effect on the total acid and total dissolved solids. The ethanol vapor and chitosan coating interaction had a significant effect on weight loss, the intensity of damage, color difference, fruit hardness, and organoleptic the flesh color, flesh taste, and the aroma of the flesh. Treatment E2C1 was the best combination because able to maintain the quality and shelf life of mangosteen fruit up to 10 days. It had the lowest value of changes in the observed parameters such as weight loss, the intensity of damage, color difference, fruit hardness, and the highest organoleptic values for color, taste, and aroma of fruit flesh. The E2C1 treatment was able to maintain the visual appearance of the fruit until the 10th day based on fruit color, texture, and damage such as fruit rot.